Settlement of Credit Agreements, For Debtors Who Deceased With Life Insurance Claims (Study Putusan Mahkamah Agung Nomor: 3079 K/Pdt/2019) - Aprillus Riwu, Hary Agung; Hafidz, Jawade (Jurnal Konstatering, 2025)
Abstract. This study, entitled Legal Review of Credit Settlement from Deceased Debtors with Life Insurance Claims (Study of Supreme Court Decision Number: 3079 K/Pdt/2019), this study aims to determine the implementation of credit settlement from deceased debtors with life insurance claims based on Law of the Republic of Indonesia Number 40 of 2014 concerning Insurance and to determine the legal protection for debtors for non-payment of claims by insurance companies against credit submitted by debtors. The approach method in this research is normative juridical, namely research conducted by emphasizing applicable regulations and literature or books related to legal relations, especially regarding. Based on the research results, it can be concluded that the implementation of credit settlement from deceased debtors with life insurance claims based on the Republic of Indonesia Law Number 40 of 2014 concerning Insurance depends on the contents of the insurance agreement stated in the insurance policy itself. And based on the Republic of Indonesia Law Number 40 of 2014 concerning Insurance Article 31 Paragraphs (3) and (4) in submitting claims, insurance companies are required to handle claims and complaints through a fast, simple, easily accessible, and fair process and are prohibited from taking actions that can slow down the settlement or payment of claims, or not taking actions that should be taken so as to result in delays in the settlement or payment of claims. Legal protection for debtors for non-payment of claims by insurance companies against credit submitted by debtors is regulated in Article 70 of Law Number 40 of 2014 concerning insurance that the Financial Services Authority has the authority to impose administrative sanctions on insurance institutions that violate the provisions of laws and regulations, and matters that cannot be violated have been clearly stated one by one in Article 71 of Law Number 40 of 2014 concerning Insurance.Keywords: Credit; Death; Insurance; Life.